(untitled) (Journal of the College of Basic Education, 2022)
There are opinions and questions; provoke reactions; And discussions that some may have found sterilefutile behind him. However, for many, such discussions are necessary in a world in which it is exacerbatedRisks insofar as the pace of science and technological inventions accelerates. It is the march of progressThe materialist who is gasping behind the culture and does not trade it. Perhaps we are studying the phenomena of risk thatIt has become one of the topics of contemporary sociology, and we cannot ignore the fact thatHuman societies, especially western ones, are facing more dangers with the expansion ofThe multiplicity of forms of terrorist phenomena. No human society seems to have managed to escapeOf the dangers and the dictates of fear and caution. Trust has been questioned. Caution is obligatoryand advance it.